HOW QUALITY INFLUENCES IN AGILITY, FLEXIBILITY, RESPONSIVENESS AND RESILIENCE IN SUPPLY CHAIN MANAGEMENT - Silva, Gilmar Lucio da [UNESP]; Rondina, Gustavo [UNESP]; Figueiredo, Paloma Cardoso [UNESP]; Prates, Glaucia [UNESP]; Savi, Antonio Francisco [UNESP] (Inst Federal Educacao, Ciencia & Tecnologia Sao Paulo, 2018)
This article aims to present the quality and its direct influence on important characteristics that dominate the Design of the Supply Network, demonstrating the main aspects involved and the strategy developed to achieve a better performance. The study is based on a literature review and the main objective of this systematic review of the literature was to identify and classify all previous studies that examined some aspect of network analysis in the context of the supply chain since so far. It provides a detailed description of the most of the subject and contributes with a set of findings that capture the current state of art of the topic. Quality in the supply chain is a new subject and little studied, but it is observed that its influence is present in all sectors of the economy. The classification of Supply Chains has been highlighted as a flow of materials and information that go from suppliers to final customers in the best possible way. With the development of a management that addresses the Supply Chain in a relevant way, the organization can achieve benefits that put it in a competitive position in the market.
Keywords: Quality; Supply Chain Management; Big Data; Agility; Flexibility; Responsiveness; Resilience